Calibration of iPad Pro LiDAR Scanning Parameters for the Scanning of Heritage Structures Using Orthogonal Arrays - Edison Atencio; Andrea Muñoz; Fidel Lozano; Jesús González-Arteaga; José Antonio Lozano-Galant (Applied Sciences)
The deterioration of historical heritage has underscored the need for precise documentation and accurate measurements in restoration and conservation efforts. Detailed documentation not only enhances understanding but also provides architects and engineers with the necessary tools to optimize these processes. However, limited funding has prompted researchers to develop low-cost geomatic tools and methodologies, such as multi-image photogrammetry, to generate 3D point clouds. Technologies like miniaturized Light Detection and Ranging (LiDAR) sensors, integrated into Apple devices such as the iPhone and iPad since 2020, have made these tools more accessible. These sensors deliver direct time-of-flight measurements, enabling accurate 3D data acquisition of historical structures. Despite the critical role that scan parameters—such as scanning speed, sensor angle, lighting, or the distance from the scanned object—may play, there is a lack of detailed studies examining their effects in the literature. To address this gap, this paper employs Taguchi’s orthogonal arrays to define the optimal scan parameters for the LiDAR sensor on the 2022 iPad Pro. The optimized parameters are then used to scan a historical building.